9-cis-Epoxycarotenoid Dioxygenase 3 Regulates Plant Growth and Enhances Multi-Abiotic Stress Tolerance in Rice - Huang, Yuan; Guo, Yiming; Liu, Yuting; Zhang, Feng; Wang, Zhikui; Wang, Hongyan; Wang, Feng; Li, Dongping; Mao, Dandan; Luan, Sheng; Liang, Manzhong; Chen, Liangbi (Frontiers in Plant Science, 2018)
Although abscisic acid (ABA) is an important hormone that regulates seed dormancy, stomatal closure, plant development, as well as responses to environmental stimuli, the physiological mechanisms of ABA response to multiple stress in rice remain poorly understood. In the ABA biosynthetic pathway, 9-cis-epoxycarotenoid dioxygenase (NCED) is the key rate-limiting enzyme. Here, we report important functions of OsNCED3 in multi-abiotic stress tolerance in rice. The OsNCED3 is constitutively expressed in various tissues under normal condition, Its expression is highly induced by NaCl, PEG, and H2O2 stress, suggesting the roles for OsNCED3 in response to the multi-abiotic stress tolerance in rice. Compared with wild-type plants, nced3 mutants had earlier seed germination, longer post-germination seedling growth, increased sensitivity to water stress and H2O2 stress and increased stomata aperture under water stress and delayed leaf senescence. Further analysis found that nced3 mutants contained lower ABA content compared with wild-type plants, overexpression of OsNCED3 in transgenic plants could enhance water stress tolerance, promote leaf senescence and increase ABA content. We conclude that OsNCED3 mediates seed dormancy, plant growth, abiotic stress tolerance, and leaf senescence by regulating ABA biosynthesis in rice; and may provide a new strategy for improving the quality of crop.